The influence of institutional environmental factors on social entrepreneurial intentions among tertiary-level students in South Africa - Kujinga, Keresia Leann (My University, 2016)
Social entrepreneurship has the potential to address and solve social problems and challenges, poverty and inequality among others, which are rife across subSaharan Africa. This academic field holds great potential, is surprisingly under researched and lagging behind in practise. A study of the influence of perceptions within the institutional environment on the decision to become a social entrepreneur is therefore critical in developing an understanding of social entrepreneurial intentions in the context of a developing and emerging economy. This study proposed to use the theory of entrepreneurial event and the institutional theory to investigate the influence of the external environment on the development of social entrepreneurial intentions and its antecedents among tertiary level students in Gauteng, South Africa. This study was quantitative and cross sectional in nature; a structured and closed-ended questionnaire was distributed electronically to the target population. 193 students participated in this study, with the final sample consisting of 128 responses. In order to analyse the data, linear multiple regression was employed. The key findings indicated that the regulatory environment has a positive and significant influence on perceived feasibility and social entrepreneurial intentions. Moreover, the findings indicated that the normative and cognitive environment have a positive but insignificant relationship with social entrepreneurship intention and its antecedents – perceived feasibility and perceived desirability. There is a negative relationship between the regulatory environment and perceived desirability, normative environment and social entrepreneurship intention, cognitive environment, perceived desirability and social entrepreneurship intention. The implications of this research for policy makers and educators is to focus on shaping the perceptions of the institutional environment as well social entrepreneurship, and the attitudes of students and society at large towards positive perceptions to influence social entrepreneurial intentions.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management specialising in Entrepreneurship and New Venture Creation, Johannesburg 2016
Keywords: Social responsibility of business--South Africa; Entrepreneurship--South Africa